2016
DOI: 10.14444/3031
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transpedicular Lumbar Endoscopy: A Case Report

Abstract: Authors found this technique very promising in complete removal of disc material under direct visualisation for high grade down disc herniations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…www.e-neurospine.org partial resection of the pedicle and facet complex, 13 other expanded applications for more complex discectomy procedures have been described. 12,14,[28][29][30][31] Controlled reaming of the superior vertebral notch or part of the pedicle did not seem to affect spinal stability and outcomes. 24 In fact, in mechanical study, the transforaminal approach produced wider decompression with less effect on stability than posterior foraminal decompression.…”
Section: ) Highly Migrated Disc Herniationmentioning
confidence: 86%
See 2 more Smart Citations
“…www.e-neurospine.org partial resection of the pedicle and facet complex, 13 other expanded applications for more complex discectomy procedures have been described. 12,14,[28][29][30][31] Controlled reaming of the superior vertebral notch or part of the pedicle did not seem to affect spinal stability and outcomes. 24 In fact, in mechanical study, the transforaminal approach produced wider decompression with less effect on stability than posterior foraminal decompression.…”
Section: ) Highly Migrated Disc Herniationmentioning
confidence: 86%
“…With modifications of the transforaminal approach, such as the mobile outside-in technique, 12 the transpedicular approach, 14 the foraminoplastic superior vertebral notch approach, 27 and The decision was made to perform right TELD L4/5 with the mobile outside-in technique, and postoperatively the patient's extensor hallucis longus strength recovered to motor grade 5. Panel A shows a sagittal view of a large sequestrated downward migrated central disc at L4/5.…”
Section: ) Highly Migrated Disc Herniationmentioning
confidence: 99%
See 1 more Smart Citation
“…Krzok et al [ 15 - 17 ] described transpedicular endoscopic surgery for highly superiorly and inferiorly migrated disc herniation and facet cysts [ 18 ]. Further case reports of Uniyal et al [ 19 ] and Quillo-Olvera et al [ 20 ] confirmed the successful use of this burr hole technique, which allows direct access to the sequestration behind the pedicle.…”
Section: Introductionmentioning
confidence: 84%
“…All these causes pressurize the nerve root which leads to the disease. The purpose of intervention in this disease is to decrease the pressure and tension applied on the nerve by removing the source of pressure [6][7][8][9][10][11][12]. The percutaneous foraminotomy introduced in this case report is a newly developed minimally invasive device that reduces pressure on the nerve root as well as the blood vessels in the neural canal.…”
Section: Discussionmentioning
confidence: 99%